COMPARATIVE ANALYSIS OF MOVING AVERAGE AND DOUBLE EXPONENTIAL SMOOTHING METHODS FOR FORECASTING ASTM A252 GR 2 PIPE DEMAND AT PT XYZ - Agustin, Ardita Dwi; Momon S, Ade; Suseno, Agustian; Maulidin, Wildan Fatchan (Center for Study and Journal Management FTI UMI, 2024)
Raw material inventory planning is a crucial aspect in the manufacturing industry to ensure smooth production and cost efficiency. However, PT XYZ has not implemented a forecasting method in its raw material planning system, so that procurement decisions are still reactive to actual demand. This study aims to analyze and compare forecasting methods using Double Exponential Smoothing (DES) and Moving Average (MA) to determine the most accurate method in projecting raw material needs for Non-API spec pipe products, type ASTM A252 GR 2 at KT 24 PT XYZ. The data used is historical demand data, which is then analyzed using POM-QM for Windows software. The results of the analysis show that the Moving Average method with a two-month period (MA-2) has the smallest Mean Squared Error (MSE), which is 182067, and a Mean Absolute Percentage Error (MAPE) value of 1.24%, which indicates a higher level of accuracy than other methods. Thus, the MA-2 method is recommended to be implemented in PT XYZ's raw material planning system to improve production efficiency and reduce the risk of excess or shortage of stock. For further research, it is recommended to develop a forecasting model by considering external factors such as market trends and seasonality, and integrating machine learning or hybrid forecasting methods to improve prediction accuracy. In addition, the implementation of an Enterprise Resource Planning (ERP)-based system with a forecasting module can also be a solution for long-term planning efficiency.